Non-Surgery Management of Globe Rupture in Rural Area: Poster Presentation - Case Report - General practitioner - Diajeng Rindang Galih Annisa; dr Dedeh Kurniasih SpM (Majalah Oftalmologi Indonesia, 2023)
Introduction : Globe rupture is a vision-threatening emergency. The management of globe rupture must arrange immediate. Case Illustration : A 59-year-old woman presented with painful and sudden vision loss on her left eye after hit by wood an hour prior. From the examination, the palpebra was oedema, and spasm, the conjunctiva was chemosis and bleeding, the sclera was laceration. Visual acuity of the left eye was 1/~. We diagnosed as globe rupture of the left eye. We gave levofloxacin injection, methylprednisolone injection, tranexamic acid injection, prednisolone eyedrop every 3 hours, levofloxacin topical every hour, and oxytetracycline eye ointment once a day in night. After 10 days, clinical manifestation was improved, but the visual acuity. From the examination, we found retinal detachment on her left eye. Patient was referred to the primary health care. Discussion : In globe rupture, infection risk is high and requires immediate systemic empiric antibiotics and surgical management. The conservative treatment was administered since the patient rejected for the globe exploration and scleral suture surgery. The aim treatment for this case is to prevent the infection. We used combination systemic and topical levofloxacin antibiotics and corticosteroid. Systemic tranexamic acid was to control the bleeding. No improvement of visual acuity after 10 days, we suspected because of retinal detachment and need surgery management. Conclusion : Surgical exploration and infection prevention are needed for globe injury. The sooner management, the better prognosis it could be.